Protective Effects of Memantine, an NMDA Receptor Antagonist, Against Cerebral Ischemia/Reperfusion Induced Injuries in Rats with Transient Congenital Hypothyroidism: Neuroprotective effects of memantine in hypothyroidism - Sepideh Ayadi; Samin Abbaszadeh; Leila Derafshpour; Ehsan Saboory; Mojtaba Karimipour; Hamid Soraya (Iranian Journal of Pharmaceutical Sciences, 2022)
Stroke is one of the major causes of mortality worldwide. Memantine, an NMDA receptor antagonist, has protective effects on neuronal cells and is important candidate as a neuroprotective agent in cerebral ischemia. On the other hand, thyroid hormones are one of the important factors in the development of the central nervous system (CNS) and its activity and the long-term adverse effects of transient thyroid function abnormalities at birth on intellectual development has been proven. Therefore, the aim of the present study was to evaluate the effects of memantine on cerebral ischemia/reperfusion (I/R) induced injuries in transient congenital hypothyroidism (TCH). The adult male Wistar TCH rats (240±20 g) were underwent forebrain ischemia by bilateral common carotid artery occlusion for 17 min. Memantine (20 mg/kg) alone or in combination with vitamin C (200 mg/kg) were administered intraperitoneally (ip) for 7 days after cerebral ischemia. Then, histopathology, cerebral infarct size and malondialdehyde level were evaluated. Histopathological analysis showed that memantine significantly decreased leukocyte infiltration in comparison to I/R group (p<0.01). Memantine also reduced infarct size and malondialdehyde level compared with I/R group (p<0.01). Memantine and vitamin C combination group had no significant effects on leukocyte infiltration, infarct size and malondialdehyde level. Our results showed that memantine through reduction in leukocyte infiltration, lipid peroxidation and infarct size could reduce cerebral ischemia/reperfusion induced injuries in transient congenital hypothyroidism. Hence, memantine might be considered as a neuroprotective agent in hypothyroidism.